Theoretical modeling of charge trapping in crystalline and amorphous Al2O3. (6th July 2017) - Dicks, Oliver A; Shluger, Alexander L
Abstract: The characteristics of intrinsic electron and hole trapping in crystalline and amorphous Al2 O3 have been studied using density functional theory (DFT). Special attention was paid to enforcing the piece-wise linearity of the total energy with respect to electron number through the use of a range separated, hybrid functional PBE0-TC-LRC (Guidon et al 2009 J. Chem. Theory Comput .5 3010) in order to accurately model the behaviour of localized states. The tuned functional is shown to reproduce the geometric and electronic structures of the perfect crystal as well as the spectroscopic characteristics of MgAl hole centre in corundum α -Al2 O3 . An ensemble of ten amorphous Al2 O3 structures was generated using classical molecular dynamics and a melt and quench method and their structural characteristics compared with the experimental data. The electronic structure of amorphous systems was characterized using the inverse participation ratio method. Electrons and holes were then introduced into both crystalline and amorphous alumina structures and their properties calculated. Holes are shown to trap spontaneously in both crystalline and amorphous alumina. In the crystalline phase they localize on single O ion with the trapping energy of 0.38 eV. In amorphous phase, holes localize on two nearest neighbour oxygen sites with an average trapping energy of 1.26 eV, with hole trapping sites separated on average by about 8.0 Å. No electron trapping is observed in the material. Our results suggest that trapping of positive charge can be much more severe and stable in amorphous alumina rather than in crystalline samples.